1997
DOI: 10.2337/diacare.20.7.1154
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hyperglycemia Is Related to Peripheral Nerve Changes at a Diabetes Duration of 4 years

Abstract: Our study indicates that sustained hyperglycemia is related to functional changes, at the minimum, in peripheral sensory and motor nerve conduction at a diabetes duration of 4 years. Our findings are consistent with a dying-back neuropathy, and there is some suggestion that chronic hyperglycemia may be more detrimental to nerves in male subjects than in female subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
(26 reference statements)
3
9
0
Order By: Relevance
“…Some studies have shown a relationship between diabetic control and NCV of separate nerves both in type 1 diabetes (12,13) and type 2 diabetes (14,15), as well as a relationship between GHb and nerve amplitudes in type 1 diabetes (13). The present study extends this knowledge by showing that, in multivariate analysis taking into account various confounding factors, the overall severity of DSP, as well as the severity of involvement in different nerve groups Qower extremities, upper extremities, motor nerves, sensory nerves), is consistently related to diabetic control.…”
Section: Results-mentioning
confidence: 99%
“…Some studies have shown a relationship between diabetic control and NCV of separate nerves both in type 1 diabetes (12,13) and type 2 diabetes (14,15), as well as a relationship between GHb and nerve amplitudes in type 1 diabetes (13). The present study extends this knowledge by showing that, in multivariate analysis taking into account various confounding factors, the overall severity of DSP, as well as the severity of involvement in different nerve groups Qower extremities, upper extremities, motor nerves, sensory nerves), is consistently related to diabetic control.…”
Section: Results-mentioning
confidence: 99%
“…Sustained hyperglycemia has been found to be related to functional changes in both peripheral sensory and motor nerve conduction at duration of diabetes of 4 years [6]. The exact mechanisms leading to nerve damage are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The actual cause of diabetic neuropathy is not well understood. Metabolic, vascular, and probably genetic factors are thought to be involved [6][7][8]. Identification of risk factors in a particular patient group is very important so that appropriate treatment can be given for prevention of further deterioration, and preventive measures can be initiated for high-risk patients to prevent foot problems.…”
mentioning
confidence: 99%
“…Furthermore, there were no significant effects on plasma glucose and GHb levels as a result of the steroid and insulin injections (results not shown). It has also been reported that nerve conduction values are related to glycemic control (Allen et al ., 1997). Plasma glucose and GHb levels were similar in both groups in our study, and did not change significantly during the course of study.…”
Section: Discussionmentioning
confidence: 93%